2021
DOI: 10.22190/fume210112027g
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Dynamics-Based Modeling of the Cavitation Dynamics in Lubricated Contacts

Abstract: Cavitation is a common phenomenon in fluid machinery and lubricated contacts. In lubricated contacts, there is a presumption that the short-term tensile stresses at the onset of bubble formation have an influence on material wear. To investigate the duration and magnitude of tensile stresses in lubricating films using numerical simulation, a suitable simulation model must be developed. The chosen simulation approach with bubble dynamics is based on the coupling of the Reynolds equation and Rayleigh-Plesset equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Khanafer et al [45] conducted Nk5000 code to explore the effect in streamlines and isotherms with changing parameters and showed that the rotational speed expressively enhances overall heat throughout the fluid than other parameters such as Ri and Re number. Geike [46] reported the cavitation phenomena in the viscoelastic fluid flows. Dolon et al [47] studied the flow analyses as well as the centrifugal influence in the duct size.…”
Section: Validation Of the Studymentioning
confidence: 99%
“…Khanafer et al [45] conducted Nk5000 code to explore the effect in streamlines and isotherms with changing parameters and showed that the rotational speed expressively enhances overall heat throughout the fluid than other parameters such as Ri and Re number. Geike [46] reported the cavitation phenomena in the viscoelastic fluid flows. Dolon et al [47] studied the flow analyses as well as the centrifugal influence in the duct size.…”
Section: Validation Of the Studymentioning
confidence: 99%
“…They revealed that reducing the cavitation number leads to a decrease in the frequency of cavity shedding. Geike [31] calculated macroscopic forces between moving rough surfaces, and the tensile stresses that affect the wear in mixed lubrication applications, and developed a model for the numerical simulation of cavitation in mixed lubrication contacts that reproduces tensile stresses on short time scales. Moreover, they identified that lower cavitation numbers correlate with higher pressure pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the microbubble dynamics near curved boundaries mainly paid attention to the bubble shape evolution and micro jet and the influence of the curvature of the curved boundary on the bubble motion. However, most early studies, as well as current work, focus on one-way coupled fluidstructure interaction with the rigid boundary [1][2][3][4] [5] [6]. We still have a lot of knowledge about two-way coupling to study.…”
Section: Introductionmentioning
confidence: 99%